Исследование макроструктуры сортовой непрерывнолитой заготовки и поведения дефектов ее осевой зоны во время прокатки - Смирнов, Е. Н.; Серов, А. И.; Скляр, В. А.; Домбровский, Е. О.; Смирнов, О. Е. (НТУ "ХПИ", 2015)
Приведены результаты заводских исследований макроструктуры сортовой непрерывнолитой сортовой заготовки из сталей 45 и У7. Установлено, что, не смотря на в целом достаточно высокое качество макроструктуры, в осевой зоне присутствует пористость и ликвация которая приводит к проблемам при последующей прокатке. С учетом выявленных дефектов осевой несплошности, разработана математическая модель и исследован процесс прокатки непрерывнолитой заготовки в обжимной клети.

Presents the results of metal macrostructure on the cross-section of continuous casting billet out of constructional steel grades. The submitted data of plant research characterize two following constructional steel grades: steel 45 according to GOST 1050-88 and Y7 according to DSTU 3833-98. The research has found that billets of current manufacturing inherent in quite high macrostructural quality. At the same time the analysis of metal macrostructure on longitudinal section has shown that quality at axial zone has unstable character. In this case, the axial number porosity and axial segregation depends to a large extent on place of specimen cutoff and can have quite wide range of variation. A mathematical model of the process of cooling and rolling continuous casting billet on the site "heating furnace – breakdown stand". The distinguishing feature is that a model takes into account the presence of axial discontinuities in continuous casting billet and scale on its surface. The model is implemented using the finite element method in the software package. As a result of the study have obtained data on the distribution of the temperature and effective stress, depending on the initial temperature of rolling and diameter of discontinuity.
Investigation of the microstructure of continuous casting billet and behavior of defects in axial zone during rolling
Keywords: сортовая заготовка; моделирование; осевая пористость; охлаждение; billets; microstructure; simulation; axial porosity; cooling; rolling